Development of Program to Enhance Working Memory Through Narrative Therapy Among Primary School Students - Leelukharanon, Areerat; Haenjohn, Juthamas; Supwirapakorn, Warakorn (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental study aimed to develop and examine the effects of a program designed to enhance working memory through narrative therapy among primary school students. The participants were 24 third-grade students selected through simple random sampling. Using a matched-pair design based on their working memory scores, the students were randomly assigned to either an experimental group or a control group, with 12 students in each group. The research instrument was a working memory enhancement program developed by the researcher, grounded in narrative theory and Multicomponent Model of Working Memory. The program was validated by five experts and revised following a pilot study prior to implementation. Data collection tools included the Corsi block test (CSBT), Forward digit span test (FWDT), Backward digit span test (BWDT) and One-back task (1BT). Data were collected in three phases: pre-test, post-test, and a four-week follow-up. Analyses were conducted using repeated-measures analysis of variance (with one between-subject and one within-subject variable), with pairwise comparisons using the Bonferroni method. The results indicated that the experimental group showed statistically significant higher working memory scores at both post-test and follow-up compared to the pre-test (P < .05). These findings suggest that the working memory enhancement program based on narrative theory can effectively improve working memory in primary school students and could be applied in educational contexts. Further research is recommended to evaluate long-term effects and broader implementation.